Potency of Some Savanna Herbaceous Weeds in the Production of Bioethanol Using Zymomonas mobilis and Saccharomyces cerevisiae (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
The uncertainty of the fossil fuel and global climate changes has invariably led to renewable energy demand. Thus, necessitating increasing biotechnological research efforts. Accordingly, the current work was designed to investigate the potency of some savanna herbaceous weeds in the production of bioethanol using Zymomonas mobilis and Saccharomyces cerevisiae. The biodiversity study and the proximate analysis of weed samples growing on Bayero University Kano old Campus, Nigeria were carried out. The substrates were pretreated with 2% of 0.233M sulfuric acid solution and hydrolysed using Aspergillus niger. The reducing sugars were estimated using the dinitrosalicylic acid method. Fermentation was carried out using local strains of Zymomonas mobilis and Saccharomyces cerevisiae isolated from fermented Zobo drink and palm wine under anaerobic conditions. The absorbance of the produced bioethanol was measured and compared with the known standard ethanol curve using Techme I Uv-vis spectrophotometry at 600nm. The dominant weeds include; Cynodon dactylon (30%), Heteropogon contortus (20%) and panicum virgatum (13.45%). The carbohydrate contents as hemicellulose ranged from (35.44 - 27.68%), cellulose (39.80 - 29.20%) and lignin contents (4.32 - 2.14%). The reducing sugar ranged from (24.67±0.01 - 94.79±0.01 mg/g) in all the substrates used. Maximum bioethanol yield was obtained with Cynodon dactylon (48.09±0.07ml/g) in fermentation with a cocktail of the microorganisms whereas, the minimum yield was observed with Heteropogon contortus (15.08±0.01 mL/g). Zymomonas mobilis had the maximum bioethanol yield (29.20±0.01ml/g) than Saccharomyces cerevisiae with (20.10±0.01 mL/g) bioethanol (p>0.05). The findings reveal the lignocellulosic weeds used in this study are good substrates which can be exploited in bioethanol production.
Keywords: Lignocellulose biomass; Pretreatment; Zymomonas mobilis; Saccharomyces cerevisiae; Bioethanol